PROTECTIVE EFFECT OF ROTENONE AGAINST LIPOPOLYSACCHARIDE AND D-GALACTOSAMINE-INDUCED HEMATOTOXICITY: Hematoprotective efficacy of Rotenone - SAMRAT RAKSHIT; ANJANI VERMA; SATENDRA KUMAR NIRALA; MONIKA BHADAURIA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study was to investigate the protective efficacy of rotenone against lipopolysaccharide (LPS) and D-galactosamine (D-GalN)-induced altered hematology. Methods: Hematotoxicity was induced by coinjection of LPS (50 μg/kg i.p.) and D-GalN (300 mg/kg i.p.). Rotenone (5, 10 and 20 mg/kg p.o.) was administered for 6 days as a pre-treatment. Blood was collected through puncturing the retro-orbital sinus to analyze blood parameter. Serum was separated to analyze glucose, triglyceride, and cholesterol. Results: The present study revealed decreased in red blood cells, platelets, hemoglobin, and hematocrit value while a significant increase in white blood cells, lymphocyte, and monocytes were observed in LPS and D-GalN treated rats. LPS and D-GalN administration significantly decrease glucose level while serum lipid profile (triglycerides and cholesterol level) were increased significantly at 5% level of significance. LPS and D-GalN-induced altered hematological and serological variables were restored toward control by rotenone pretreatment for 6 days in dose-dependent manner. Conclusion: It can be said that LPS and D-GalN administration resulted in alteration of various hematological parameters and rotenone at 20 mg/kg dose restored significant alteration toward control due to the presence of antioxidant activity of rotenone.